Implications of quantal response statistical equilibrium - Ellis Scharfenaker (The University of Utah, Department of Economics, 2019)
This paper explores the foundations and properties of the quantal response statistical equilibrium (QRSE) model developed by Scharfenaker and Foley (2017). The QRSE model provides a behavioral foundation for the formation of aggregate economic outcomes in social systems characterized by negative feedbacks. It can approximate a wide range of commonly encountered theoretical distributions that have been identified as economic statistical equilibrium and displays qualitatively similar behavior to the Subbotin and Asymmetric Subbotin distributions that range from the Laplace to the Normal distribution in the limit. Asymmetry in the frequency distributions of economic outcomes arises from the unfulfilled expectations of entropy-constrained decision makers. This paper demonstrates the logic of the QRSE model in an application to US stock market data dating back to 1926. The model provides a parsimonious explanation for the distribution of rates of return on private equities as well as clear behavioral foundation for asset price fluctuations.
Keywords: C1; C18; C70; D8; 330; QRSE; Quantal response; Maximum entropy; Statistical equilibrium; Information theory